The analytical control issues of platinum metals production - Yu. A. Karpov; E. S. Danilin; V. B. Baranovskaya; N. A. Arakelyan; N. E. Khar’kov; V. P. Karmannikov (Тонкие химические технологии)
This article is devoted to the analytical control issues of platinum metals production and their solution based on complex approach to the optimization of sampling, sample preparation and analysis stages